Critical analysis of the problems of Islamic education in the era of disruption - Firman, Arham Junaidi; Ni'mah, Ulfatun (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
The world of Islamic education in the disruptive era faces fundamental problems. This research critically analyzes these challenges using a literature study with a philosophical approach. Data were collected through documentation techniques for relevant references and using content analysis. The findings highlight vital issues about the relevance and accessibility of Islamic education in the era of disruption. Challenges include aligning or relevance of Islamic education with the evolving job market, societal needs, and technological advancements. Barriers to access to Islamic education include inadequate facilities, information dissemination gaps, transportation issues, teacher quality, and underrepresentation in marginalized groups and 3T areas. The government has implemented policies such as Merdeka Belajar-Kampus Merdeka, compulsory education, BOS funds, Indonesia Smart Card, frontline teachers, and zoning-based new student admissions. Practical challenges include differences of opinion, program incompatibility, limited public awareness, and complexity. This study provides valuable insights into Islamic education, emphasizing the need for continuous evaluation and improvement to create Indonesia's inclusive, responsive and effective Islamic education system. Addressing these challenges will better equip the Islamic education framework to navigate the disruptive era successfully.